1986
DOI: 10.1007/bf00452065
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ADP-induced platelet aggregation in diabetes mellitus

Abstract: ADP-induced platelet aggregation was measured in 15 Type 1 (insulin-dependent) diabetic patients, 15 Type 2 (non-insulin-dependent) diabetic patients and in 15 non-diabetic control subjects. Simultaneous measurements were made of fasting blood glucose, glycosylated haemoglobin, serum insulin, total plasma cholesterol, cholesterol in the lipoprotein subfractions, total triglycerides and platelet phospholipid fatty acid levels. Regression analysis of aggregation against the biochemical variables within the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Increased sensitivity of platelets from diabetic patients to ADP-, PAF-, and AA-induced aggregation compared with healthy subjects has been reported. [31][32][33] The effect of glycemic control on platelet aggregation has also been documented, suggesting that improvement in glycemic control is followed by reduced sensitivity of platelets to aggregation. 32,34 Our results demonstrate that diet composition can influence the aggregatory response of platelets.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increased sensitivity of platelets from diabetic patients to ADP-, PAF-, and AA-induced aggregation compared with healthy subjects has been reported. [31][32][33] The effect of glycemic control on platelet aggregation has also been documented, suggesting that improvement in glycemic control is followed by reduced sensitivity of platelets to aggregation. 32,34 Our results demonstrate that diet composition can influence the aggregatory response of platelets.…”
Section: Discussionmentioning
confidence: 96%
“…[31][32][33] The effect of glycemic control on platelet aggregation has also been documented, suggesting that improvement in glycemic control is followed by reduced sensitivity of platelets to aggregation. 32,34 Our results demonstrate that diet composition can influence the aggregatory response of platelets. Specifically, the EC 50 values of PAF and ADP were higher in both healthy subjects and T2DM patients after the 1-month consumption of traditional Greek diet, indicating that their platelet function had improved.…”
Section: Discussionmentioning
confidence: 96%
“…Activated phospholipase C causes rapid hydrolysis of phosphoinositides and consequently produces inositol phosphates and diacylglycerol (7,8). It has been documented that platelet aggregability is positively correlated with fasting blood glucose level (2,24). These findings were coupled with significantly enhanced accumulation of PA, which may be generated from diacylglycerol by diacylglycerol kinase (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…26 Of interest in the present study is that ADP-induced platelet aggregation was positively and independently correlated with blood glucose, a finding also reported for diabetes. 27 It has also been shown that platelets from diabetic patients are hypersensitive to agonists such as ADP 28 and are resistant to the inhibitory effect of aspirin, 28 as also described in diabetic animals 29 and HTRs. 30 Another similarity between diabetic and transplanted patients is their tendency to develop intramyocardial small-vessel disease, as shown by pathological examination 1 and coronarography.…”
Section: Platelet Aggregation Relation To Other Clinical and Biologicmentioning
confidence: 94%